2020
DOI: 10.3390/nu12123687
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Changes in Food Addiction Symptoms and Body Weight among Adults in a Behavioral Weight-Loss Program

Abstract: Interest in food addiction (FA) has increased, but little is known about its clinical implications or potential treatments. Using secondary analyses from a randomized controlled trial, we evaluated the associations between changes in FA, body weight, and “problem food” consumption during a 22-month behavioral weight-loss program consisting of an initial four-month in-person intervention, 12-month extended-care, and six-month follow-up (n = 182). Food addiction was measured using the Yale Food Addiction Scale. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 66 publications
1
6
0
Order By: Relevance
“…Our results indicate that the presence of FA at baseline resulted in a significant higher weight regain after three years, when following a Mediterranean diet. These findings are consistent with prior research that observed an association between the presence of FA and worse results while seeking a weight loss [ 71 , 72 , 73 ]. Previous results from our group showed that among individuals with obesity seeking bariatric surgery, the presence of FA at baseline predicted poorer weight loss achievement after a dietary and lifestyle intervention before the surgical intervention [ 6 ].…”
Section: Discussionsupporting
confidence: 92%
“…Our results indicate that the presence of FA at baseline resulted in a significant higher weight regain after three years, when following a Mediterranean diet. These findings are consistent with prior research that observed an association between the presence of FA and worse results while seeking a weight loss [ 71 , 72 , 73 ]. Previous results from our group showed that among individuals with obesity seeking bariatric surgery, the presence of FA at baseline predicted poorer weight loss achievement after a dietary and lifestyle intervention before the surgical intervention [ 6 ].…”
Section: Discussionsupporting
confidence: 92%
“…This special issue presents a collection of articles, contributed by renowned experts, researchers, and clinicians spanning different disciplines, that adds to the knowledge on the clinical utility of food addiction and eating addiction. The articles in this collection include reviews [1][2][3][4][5] as well as original research utilizing a variety of methodologies and study designs such as clinical trials [6][7][8], cross-sectional studies [9,10], and surveys [11].…”
mentioning
confidence: 99%
“…In a sample of individuals with obesity and binge eating disorder participating in a behavioural weight loss program, Wiedemann et al [7] found that those with food addiction reported a stronger negative reaction to weekly weighing and less acceptance of their weight and shape throughout treatment, and the authors recommended that body image concerns be targeted in treatment given that both of these factors prospectively predicted greater eating disorder psychopathology. Gordon et al [8] found that food addiction symptoms improved during a behavioural weight loss program; however, more severe food addiction symptomatology was associated with less weight loss. Interestingly, reduced intake of hyperpalatable foods during the program was associated with short-term improvements in food addiction symptoms but not with long-term improvements in food addiction symptoms or weight, suggesting that the association among hyperpalatable foods, food addiction, and weight is a complex one.…”
mentioning
confidence: 99%
“…This special issue presents a collection of articles, contributed by renowned experts, researchers, and clinicians spanning different disciplines, that adds to the knowledge on the clinical utility of food addiction and eating addiction. The articles in this collection include reviews [ 1 , 2 , 3 , 4 , 5 ] as well as original research utilizing a variety of methodologies and study designs such as clinical trials [ 6 , 7 , 8 ], cross-sectional studies [ 9 , 10 ], and surveys [ 11 ].…”
mentioning
confidence: 99%
“…In a sample of individuals with obesity and binge eating disorder participating in a behavioural weight loss program, Wiedemann et al [ 7 ] found that those with food addiction reported a stronger negative reaction to weekly weighing and less acceptance of their weight and shape throughout treatment, and the authors recommended that body image concerns be targeted in treatment given that both of these factors prospectively predicted greater eating disorder psychopathology. Gordon et al [ 8 ] found that food addiction symptoms improved during a behavioural weight loss program; however, more severe food addiction symptomatology was associated with less weight loss. Interestingly, reduced intake of hyperpalatable foods during the program was associated with short-term improvements in food addiction symptoms but not with long-term improvements in food addiction symptoms or weight, suggesting that the association among hyperpalatable foods, food addiction, and weight is a complex one.…”
mentioning
confidence: 99%